Emerging Trends in the Regulation of Social Security - Anifalaje, Kehinde (Journal of Malaysian and Comparative Law, 2016)
This paper explores the trend in the regulation of social security in the developed and developing countries with special attention placed on three major policy areas of social security, namely, coverage, benefit structure and financing. It also discusses several policy options within social security provisions in particular, old age, medical, sickness, unemployment and work injury, in the light of fiscal and administrative constraints. The paper argues that social security is realistically, a functional institution in a developed country. It has been used as a means for promoting political, social and economic stability and for securing a myriad of accompanying advantages that have consequentially resulted in high standards of living. It concludes that developing countries, especially those in sub-Saharan Africa, need to improve their social security schemes (by enacting laws that are more adaptable to the socio-economic realities of the region) and commit to an increased budgetary allocation for social security (as seen in developed communities) in order to enhance social protection for the populace in respect of a defined contingency.